Employee-Owned Firms and the Careers of Young Workers - Gabriel Burdin; Jose Garcia-Louzao (CESifo GmbH, 2025)
Using detailed administrative data from Spain, we characterize how a first work experience in an employee-owned firm (EOF) versus a conventional firm can affect workers' careers. We find that workers' exposure to EOFs at the time of entry reduces daily wages by 8% over the first 15 years in the labor market. The wage penalty appears to be driven by differences in job mobility and wage returns to experience rather than by non-random selection. We show that workers who had their first job in EOFs have a strong attachment to this organizational model and are less likely to experience both voluntary and involuntary job separations over their careers, with quit and layoff rates 8% and 4% lower, respectively. In addition, we quantify lower wage returns to experience in EOFs, although there are no differences in subsequent career progression in terms of promotions. Taken together, the analysis suggests the existence of other job amenities offered by EOFs that may compensate for flatter wage profiles.
Keywords: J31; J50; J62; 330; employee-owned firms; careers; wages; job mobility